Inadequate Hand Washing, Lack of Clean Drinking Water and Latrines as Major Determinants of Cholera Outbreak in Somali Region, Ethiopia in 2019 - Jemal Mussa Challa; Tamirat Getachew; Adera Debella; Melkamu Merid; Genanaw Atnafe; Addis Eyeberu; Abdi Birhanu; Lemma Demissie Regassa (Frontiers Media S.A., 2022)
IntroductionCholera remains a serious public health problem characterized by a large disease burden, frequent outbreaks, persistent endemicity, and high mortality, particularly in tropical and subtropical low-income countries including Ethiopia. The recent cholera outbreak in the Somali region began on 4 September to 1 November 2019. Cholera may spread rapidly through a population so that an early detection and reporting of the cases is mandatory. This study aimed to identify determinants of cholera infection among >5 years of age population in Somali region, Ethiopia.MethodsA community-based unmatched case-control study was conducted among 228 (76 cases and 152 controls, 1:2 ratio) systematically selected population. Data were collected using a structured questionnaire administered by an interviewer and a record review. Descriptive statistics and multivariable logistic regression analysis was used to identify the determinants of the risk factors of cholera infection with a 95% confidence interval and statistical significance was declared a tap-value < 0.05.ResultsA total of 228 participants (33.3% cases and 66.7% controls) were enrolled in this study. The majority of the cases were in the range of 20-49 years of age (69.7%). The odds of acquiring cholera infection increased significantly by drinking unsafe pipe water (AOR 4.3, 95% CI 1.65-11.2), not having a household level toilet/latrine (AOR 3.25, 95% CI 1.57-6.76), hand washing only sometimes after the toilet (AOR 3.04, 95% CI 1.58-5.86) and not using water purification methods (AOR 2.3, 95% CI 1.13-4.54).ConclusionMajor risk factors for cholera infection were related to drinking water and latrine hygiene. Improvement in awareness creation about cholera prevention and control methods, including water treatment, hygiene and sanitation were crucial in combating this cholera outbreak. Primary public health actions are ensuring clean drinking water, delivery of water purification tablets, soap and hand sanitizers and provision of health care and outbreak response. Long term goals in cholera affected areas include comprehensive water and sanitation strategies. Overall, the strategic role of a multi-sectoral approach in the design and implementation of public health interventions aimed at preventing and controlling cholera are essential to avert cholera outbreaks. Preparedness should be highlighted in cholera prone areas like Somali region especially after drought periods.